Registro de coloración anormal del oso hormiguero norteño Tamandua mexicana (Saussure, 1860) y notas sobre su límite sur de distribución - More, Alexander (2021)
We present the record of an individual of northern tamandua (Tamandua mexicana) with abnormal white coloration that was photographed with a camera trap in the equatorial dry forest in the department of Lambayeque, at elevation of 560 m, northwest Peru. We could not determine if this chromatic aberration was a case of leucism or albinism, but we highlight this uncommon record as the first for Peru. We also revised the information about its presence in the southern portion of its global range.